UPAYA MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN AGAMA HINDU MELALUI PENERAPAN MODEL PEMBELAJARAN COOPERATIF LEARNING PADA SISWA KELAS VI SD NEGERI 4 TENGANAN - I MADE SUBAWA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This research was carried out at SD Negeri 4 Tenganan in Class VI where the ability and learning outcomes of students for Hindu Religious Education subjects were quite low. Midterm of the 2020/2021 Academic Year. This study uses two rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this study was the Class VI students of SD Negeri 4 Tenganan, totaling 12 consisting of 4 male students and 8 female students. The data obtained were in the form of formative test results, observation sheets for teaching and learning activities. can improve student achievement and learning activity in learning Hinduism marked by student understanding with the percentage value of increasing the average grade value in the pre-cycle to cycle I and from cycle I to cycle II respectively 4.64% and 20.32%, namely from the average value of class 71 in the pre-cycle to 74.3 in the first cycle and in the second cycle to 89.4. The achievement of the percentage increase in absorption is the same as the percentage of the average grades from pre-cycle to cycle I and from cycle I to cycle II are